Emergence of Competitive Dominant Ammonia-Oxidizing Bacterial Populations in a Full-Scale Industrial Wastewater Treatment Plant - Layton, Alice C. (American Society for Microbiology, 2005)
Ammonia-oxidizing bacterial populations in an industrial wastewater treatment plant were investigated with amoA and 16S rRNA gene real-time PCR assays. Nitrosomonas nitrosa initially dominated, but over time RI-27-type ammonia oxidizers, also within the Nitrosomonas communis lineage, increased from below detection to codominance. This shift occurred even though nitrification remained constant.